2014
DOI: 10.5897/ajar11.691
|View full text |Cite
|
Sign up to set email alerts
|

Growth, nodulation and yield components of mung bean (Vigna radiata) as affected by phosphorus in combination with rhizobium inoculation

Abstract: Mungbean (Vigna radiata L.) is capable of fixing atmospheric nitrogen through bacteria living in its root nodules. To study the influence of phosphorus (P) fertilization and Rhizobium inoculation on the nodulation, growth and yield of mungbean (Vigna radiata), a pot experiment was conducted in wire house, during spring season of 2010 at University of Agriculture, Faisalabad. A composite soil sample was collected from the research area and analysis of physical and chemical properties of the soil was done. Seeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Anjum, Ahmed, and Rauf (2006) reported that Rhizobium inoculation of mungbean seeds increased the number of pods per plant, number of seeds per plant, seed weight and seed yield over the control. Rhizobium inoculation also increased plant height, number of nodules per plant, number of pods per plant, number of seeds per pod and weight of seeds per plant, and N and phosphorous (P) accumalation compared to the control (Hussain et al, 2014). Molla, Solaiman, Jahiruddin, Mridha, and Khanam (2011) observed that inoculation of seed with Rhizobium produced a higher number of nodules per plant, plant height, number of pod per plant and seed yield.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Anjum, Ahmed, and Rauf (2006) reported that Rhizobium inoculation of mungbean seeds increased the number of pods per plant, number of seeds per plant, seed weight and seed yield over the control. Rhizobium inoculation also increased plant height, number of nodules per plant, number of pods per plant, number of seeds per pod and weight of seeds per plant, and N and phosphorous (P) accumalation compared to the control (Hussain et al, 2014). Molla, Solaiman, Jahiruddin, Mridha, and Khanam (2011) observed that inoculation of seed with Rhizobium produced a higher number of nodules per plant, plant height, number of pod per plant and seed yield.…”
Section: Introductionmentioning
confidence: 98%
“…However, under unfavorable conditions such as very acidic and heavy-textured soils, or very hot, dry conditions, Rhizobium survival and crop establishment can be constrained, thereby limiting root nodulation and yield (Kirchhof & So, 1995;Rahmianna, Adisarwanto, Kirchhof, & So, 2000). Therefore, seed inoculation with a strain of Rhizobium, appropriate to the cultivar and soil texture is recommended for improving growth and yield of mungbean (Hussain et al, 2014;Sharma & Khanna, 2010). Anjum, Ahmed, and Rauf (2006) reported that Rhizobium inoculation of mungbean seeds increased the number of pods per plant, number of seeds per plant, seed weight and seed yield over the control.…”
Section: Introductionmentioning
confidence: 99%